2010
DOI: 10.1517/17425247.2010.538679
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency sonophoresis: application to the transdermal delivery of macromolecules and hydrophilic drugs

Abstract: Importance of the field-Transdermal delivery of macromolecules provides an attractive alternative route of drug administration when compared to oral delivery and hypodermic injection, because of its ability to bypass the harsh gastro-intestinal tract and deliver therapeutics noninvasively. However, the barrier properties of the skin only allow small, hydrophobic permeants to traverse the skin passively, greatly limiting the number of molecules that can be delivered via this route. The use of low-frequency ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(102 citation statements)
references
References 95 publications
1
96
0
5
Order By: Relevance
“…Using LFS, the large bubbles form outside the skin, become unstable and implode powerfully near the solid stratum corneum surface resulting in a jet of fluid, referred to microjet. When these microjets affect the stratum corneum, they erode the dead cells and help to permeate the membrane [35][36][37]. Tang et al definitively demonstrated by an experimental study that ultrasound-induced cavitation is the key mechanism via which LFS permeates the skin.…”
Section: Sonophoresismentioning
confidence: 99%
“…Using LFS, the large bubbles form outside the skin, become unstable and implode powerfully near the solid stratum corneum surface resulting in a jet of fluid, referred to microjet. When these microjets affect the stratum corneum, they erode the dead cells and help to permeate the membrane [35][36][37]. Tang et al definitively demonstrated by an experimental study that ultrasound-induced cavitation is the key mechanism via which LFS permeates the skin.…”
Section: Sonophoresismentioning
confidence: 99%
“…To date, LFS has been shown to enhance dermal penetration of various other macromolecules including cyclosporine A [74], antisense oligonucleotides [75] and tetanus toxoid [76] as well as a large number of small molecules. For a detailed list of studied molecules, see Polat et al [77]. Lopez 11 , Seto 12 , Blankschtein and Langer also showed that LFS can enhance the delivery of nanoparticles into the skin.…”
Section: Sonophoresismentioning
confidence: 99%
“…However, clinical uses of LFS are relatively rare, with only a few current applications in patients because of the lack of historical precedence of safety. Examples of biological molecules delivered transcutaneously by the use of LFS are summarized in Table 22.3 [250].…”
Section: Ultrasound-mediated Transdermal Deliverymentioning
confidence: 99%